2009
DOI: 10.2174/1874918600902010001
|View full text |Cite
|
Sign up to set email alerts
|

Population Growth and Economic Development in Pakistan

Abstract: There is divergence of opinion regarding the consequences of population growth for economic development. Some view rapid population growth as a real problem while others assert that it is not a matter of grave concern. Crossnational evidence on the relationship between population growth and economic growth is inconsistent because the underlying parameters and assumptions vary across countries. Country-specific studies are more useful for illuminating unique features of a country. In this article, I examine Pak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 9 publications
5
40
0
2
Order By: Relevance
“…Gender ratio is positively skewed which shows that the mean and median value of data tend toward right. Above results are in agreement with the study of Afzal (2009 All our variables are significant at 5% and 10% confidence interval. The probability of F-Statistics value is 0.0002 which completely explains the correctness of selection of variable (Value is not negative) and Singular F-stat is within range of 10 that is 7.55.…”
Section: Box Plot Shows the Existence Of Extreme Values In The Data Osupporting
confidence: 93%
See 2 more Smart Citations
“…Gender ratio is positively skewed which shows that the mean and median value of data tend toward right. Above results are in agreement with the study of Afzal (2009 All our variables are significant at 5% and 10% confidence interval. The probability of F-Statistics value is 0.0002 which completely explains the correctness of selection of variable (Value is not negative) and Singular F-stat is within range of 10 that is 7.55.…”
Section: Box Plot Shows the Existence Of Extreme Values In The Data Osupporting
confidence: 93%
“…This shows that by increasing female employment (FE) and female literacy (FL) we can get rid of lopsided gender ratio. This study is in line with the studies of Afzal (2009). Both these authors argued that only hope for women to achieve any kind of equality in India and in Pakistan is to increase educational, economic opportunities and enhancement of social status for females.…”
Section: Box Plot Shows the Existence Of Extreme Values In The Data Osupporting
confidence: 89%
See 1 more Smart Citation
“…Some studies have found that population growth has a positive relationship with economic growth and this was supported by Savas (2008), Furuoka (2009) and Furuoka and Munir (2011). However, Afzal (2009) and Trang and Hieu (2011) found a negative relationship between population growth and economic growth. In addition, some of the studies such as Dawson and Tiffin (1998) for India, Thornton (2001) for seven Latin American countries, and Mushtaq (2006) for Pakistan indicated that there were no long run cointegrating relationship between population and economic growth.…”
Section: Previous Studiesmentioning
confidence: 97%
“…Reduction in per capita income is linked with overall access to health and education. Some other investigators concludes that population growth adversely affects the economic growth; it consumed most of our resources (Afzal, 2009). Urbanization is another challenge for Pakistan, currently 38 percent population are residing in urban areas as compared to 29 percent in 1981.…”
Section: Implications Of Rapid Population Growthmentioning
confidence: 99%